Structure of Science Teacher Education in PISA Leading Countries: A Systematic Review - Melina Doil; Verena Pietzner (MDPI AG, 2023)
Within the surveys of the PISA study since 2001, large differences between the performance of the 15-year-old students in the scientific domain have become apparent. German students were able to improve their performance to a limited extent in the past surveys, despite extensive educational reforms. Despite the improvement in performance, Germany has not been able to catch up with the PISA-leading countries. Therefore, the question arises in regard to how teacher education in PISA leading countries (Canada, Finland, Japan, Singapore) is structured. The selection of the countries is based on best possible achieved results in the scientific competence area as well as in another competence area by the selected countries. A systematic review was conducted to clarify the structure as well as relevant content issues. The results indicate various possibilities for adaptation for German teacher education.